The Oppenness of Society: the Nature and the Basic Characteristics - Yatsura, Katerina (Visnyk of V. N. Karazin Kharkiv National University. Series Sociological studies of contemporary society: methodology, theory, methods, 2019)
In the article conceptualization of the notion of society openness is executed in the sociological context. The category “openness” is considered; distinctive features of the concepts of “openness” and “transparency” are identified. The basic characteristics of society openness are determined. Open society is explicated as a society aimed at development and innovations, in contrast to closed society aimed at reproduction of traditional forms of existence. The basic stages of formation of the open society concept are considered.